Advances in immune checkpoint inhibitor combination strategies for microsatellite stable colorectal cancer - Ros, Javier; Balconi, Francesca; Baraibar, Iosune; Saoudi Gonzalez, Nadia; Salva, Francesc; Tabernero, Josep; Elez, Elena (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors have reshaped the prognostic of several tumor types, including metastatic colorectal tumors with microsatellite instability (MSI). However, 90-95% of metastatic colorectal tumors are microsatellite stable (MSS) in which immunotherapy has failed to demonstrate meaningful clinical results. MSS colorectal tumors are considered immune-cold tumors. Several factors have been proposed to account for this lack of response to immune checkpoint blockade including low levels of tumor infiltrating lymphocytes, low tumor mutational burden, a high rate of WNT/β-catenin pathway mutations, and liver metastases which have been associated with immunosuppression. However, studies with novel combinations based on immune checkpoint inhibitors are showing promising activity in MSS colorectal cancer. Here, we review the underlying biological facts that preclude immunotherapy activity, and detail the different immune checkpoint inhibitor combinations evaluated, along with novel immune-based therapies, to overcome innate mechanisms of resistance in MSS colorectal cancer.